(untitled) (Revista Contexto & Saúde, 2023)
The objective of the present study was to analyze the expansion of the offer of dental prostheses by the Oral Health Teams (ESB) according to Brazilian geographic regions. The time series study was carried out with secondary data from Module II of the 1st cycle (2011-2012), Module VI of the 2nd cycle (2013-2014) and Module V and VI of the 3rd cycle (2015-2018) of the External Assessment instrument of the Program to Improve Access and Quality of Primary Care (PMAQ-AB). Proportions were compared between Brazilian regions using the Chi-square test, and between years using the Cochran Q test, using the z test adjusted by the Bonferroni method (p<0.05). The identification of users in need of a prosthesis increased among the ESB in Brazil between 2012 (50.5%) and 2014 (52.4%) (p=0.001), with an increase in the Northeast (p<0.001) and a decrease in the Center- West (p=0.01). Prosthesis delivery and its follow-up decreased in Brazil in 2014 (7.7%) compared to 2012 (13.0%) and 2018 (13.5%) (p<0.001), with an increase in 2018 in the Northeast (p<0.001). In Brazil, the supply of Complete Dentures increased from 2012 (35.9%) to 2014 (42.4%), with the exception of the Midwest region (p>0.05). Removable Partial Dentures increased in Brazil from 2012 (25.7%) to 2014 (30.5%) (p<0.001), and increased in the South and Northeast (p<0.05). There was an increase in ESBs offering dental prosthesis services in Primary Care, however, there are still disparities between geographic regions.